Short-term trends in suspended particulate matter (SPM) concentrations in Kuala Lumpur, Malaysia, from 1992-1995 - Mohamed Elnour Yassen (Environmental Management Society, Malaysia, 2002)
The purpose of this study is to show the significant variations including annual, seasonal, monthly and day-to-day patterns of SPM in Kuala Lumpur for the period 1992 to 1995 in order to understand the short-term trends. The study has shown that the SPM in Kuala Lumpur was significantly high with the average value ranging from 54 to 85µg m-3, and a maximum of 300 µg m-3 was recorded. The monthly mean concentrations coincide well with seasonal cycle with higher values occurring during the month of dry seasons and lower concentrations during rainy seasons. The seasonal mean SPM concentrations showed the maximum occurring during southwest monsoon and inter-monsoon (Oct.-Nov.) with approximately 69 µg m-3 whereas the minimum during northeast monsoon 49 µg m-3 . The maximum daily average in 1993 (281 µg m-3) was 187% of Malaysia standard (150 µg m-3 for 24-hour mean) and 374% of WHO standard. The daily maximum concentrations for 1995 was 96µg m-3, this is significantly lower than the daily maximum for 1993. Air quality has greatly improved in 1995 in the area, for example the number of days with SPM pollution above the Malaysia standard (150 µg m-3 for 24-hour), declined from 15 days in 1993 to none in 1995